Interpretation of “Ngahiang” Prabu Siliwangi in Babad Tanah Sunda Cirebon - Adiwinata, Syan Rosyid; Nabilah, Siti (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
The purpose of this study is to scientifically reveal the meaning of Prabu Siliwangi's “Ngahiang” which appears in the Babad Tanah Sunda Babad Cirebon. Not only in the Babad, but this is in several history books (Historiography) especially those that review the fall of the Pajajaran Kingdom. This research focuses on finding the truth of the meaning of Prabu Siliwangi's “Ngahiang” and also so that it can be rationally accepted about several possibilities of Prabu Siliwangi's existence at that time the Pajajaran Kingdom was being visited by the Cirebon Sultanate. This research method uses literature studies from relevant historiography as well as from journal articles and news that review Prabu Siliwangi as well as archaeologically valid historical sites. Researchers use the philological method approach as the main source and also anthropology. Data analysis also uses Descriptive Qualitative so that this article can describe phenomena or events that are currently taking place. The result of this research is that the meaning of the word “Ngahiang” of Prabu Siliwangi is not moksa or disappearing without a trace from the face of this earth but there are natural causes, including illness due to old age.